Assessing electronic personal health information use: An update on progress toward healthy people 2020 objectives. Issue 3 (September 2019) - Greenberg-Worisek, Alexandra J.; Kurani, Shaheen; Finney Rutten, Lila J.; Blake, Kelly D.; Moser, Richard P.; Hesse, Bradford W.
Highlights: Public interest in personal use of health information technology (HIT) is increasing. HIT for personal use is a key national objective in Healthy People 2020. Disparities exist in access to and use of HIT for many sociodemographic groups. Notable disparities are found by sex, education, income, and geography. These disparities need to be considered in creating targets for Healthy People 2030. Abstract: Objective: To assess progress toward Healthy People 2020 health information technology objectives using nationally representative data. Methods: We used data from six administrations (2003–2017) of the Health Information National Trends Survey (HINTS) to examine trends in the proportion of Americans who manage electronic Personal Health Information (ePHI) and email their healthcare providers. Two targets were evaluated: (1) a goal to exceed 15.7% of the general population for accessing ePHI (10% improvement), and (2) a goal to exceed 15% for communicating with health providers (10% improvement). Analyses included bivariate and multivariable logistic regression models, including assessing predicted marginal for key sociodemographic variables to explain observed digital divides in health information technology use over time. Results: Self-reported management of ePHI online significantly increased between 2008 and 2017 from 14.2% to 70.9% ( p < 0.001; HP2020 target = 15.7% by 2020). Use of email to connect with healthcare providers also significantly increased, from 7.0% in 2003 to 41.1% in 2017 ( p < 0.001; HP2020 target = 15.0% by 2020). Multivariable regression revealed significant differences by sex, age, race/ethnicity (ePHI only), education, income, and geography over time. Conclusions: Targets set forth in HP2020 were exceeded for these health information technology objectives. Though an increase in adoption of these tools was seen across all sociodemographic categories, disparities persist and have even widened for certain groups. As efforts move forward to set targets for HP2030, the persistence of the digital divide amongst these groups should be considered.